Pengembangan Sistem Pendampingan Usaha Berkelanjutan Bagi UMKM Berbasis Sistem Manajemen Kinerja - Mohammad Riza Radyanto; Endro Prihastono (OPSI, 2020)
During 2015-2018, Micro and Small and Medium Enterprises (MSMEs) entrepreneurs are faced with complex and multidimensional business problems influenced by internal and external factors. they are faced with problems that are classified into 5 main problems: marketing, finance, product legality, human resources, and packaging. The limited number of workers also affects business performance, where the average number of operators is 1-3 people per MSME, so steps are needed to maintain business performance namely through business assistance by outsiders. The purpose of this research is to produce a new system in the form of a continuous business assistance model involving 5 elements Penta helix: government, academia, business, community, and business assistants. The method used is a case study, a literature study based on gap analysis of previous research. The results obtained from this study are a new system in the form of a sustainable assistance model with 23 key performance indicators from 5 aspects of business based on a Performance Management System. In the future with this system, it is expected that Indonesian MSMEs have business resilience and sustainability.